Analisis Markov untuk Perpindahan Merk Kartu GSM - Jeni Marianti Loban (Jurnal Ilmiah Wahana Pendidikan, 2022)
Markov chain method produces probabilistic information that can be used to assist decision making. In Markov analysis, an equilibrium state is a condition in which a variable in the system ultimately carries a transition probability in a stable or unchanged state. This study aims to determine the opportunities for consumers to move from GSM cellular card brands to other GSM cellular card brands and to predict the opportunities for consumers to move GSM cellular card brands among students in the future. The data used in this study is primary data collected through the distribution of questionnaires to students of the Mathematics and Natural Sciences Faculty, Tribuana Kalabahi University. The total sample in this study was 82 students. Based on the results of the study, it was found that the Simpati card brand was the card brand that was most widely used by FMIPA students in the future with a total of 94.6% of respondents. while the XL card brand has a 5.4% chance of moving in the future. and the US card brand has a 0% chance of moving in the future. The situation will be balanced for each card brand will remain in the 6th period.